2021
DOI: 10.1088/1757-899x/1088/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis of COVID-19 vaccine in Indonesia using Naïve Bayes Algorithm

Abstract: As of January 2021, with 2,066,175 deaths, 95,612,831 confirmed cases have been reported globally. Indonesia’s COVID-19 Task Force report shows that there are currently 27,203 deaths, with reported cases exceeding 951,651, among the highest in Asia. The President of the Republic of Indonesia created a national team to speed up the production of vaccines for COVID-19. It stipulates that the government will arrange the provision, delivery, and vaccination of COVID-19 vaccines. The vaccination scheme would then b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 11 publications
1
25
0
6
Order By: Relevance
“…The frequency with which the word appears in papers demonstrates its popularity. Thus, the weight of the relationship between a word and a document will be greater if the term occurs frequently in the document and the document collection as a whole has few instances of the word [11]. The TF-IDF value is calculated by multiplying the two equations as follows:…”
Section: Term Frequency -Inverse Document Frequency (Tf-idf)mentioning
confidence: 99%
“…The frequency with which the word appears in papers demonstrates its popularity. Thus, the weight of the relationship between a word and a document will be greater if the term occurs frequently in the document and the document collection as a whole has few instances of the word [11]. The TF-IDF value is calculated by multiplying the two equations as follows:…”
Section: Term Frequency -Inverse Document Frequency (Tf-idf)mentioning
confidence: 99%
“…Researchers make use of these opinions to analyze the sentiments of peoples on various issues like politics, sports, product reviews etc., The emotions expressed by the Twitter community during 2020 has been used to understand the people sentiments during a pandemic [7][8][9][10][11][12].…”
Section: Connect To Twitter and Authenticationmentioning
confidence: 99%
“…It is found that fear is significant in the discussion about covid-19. In the paper [5], Twitter data is extracted manually by data crawling using Twitter API access token with "Vaccine" and "COVID-19" as keywords. Naïve Bayes algorithm is used for sentiment analysis and is found that the majority of the tweets have a negative sentiment.…”
Section: Introductionmentioning
confidence: 99%